Rural nutrition interventions with indigenous plant foods: A case study of vitamin A deficiency in Malawi - Babu, Suresh Chandra (2000)
Identification, propagation, and introduction of a nutritionally rich, indigenous plant species in the existing cropping system are presented in this paper as a method of rural nutrition intervention. A case study of Moringa (Moringa oleifera Lam., Moringaceae), which is a common tree in Malawi and one of the richest sources of vitamin A and vitamin C compared to the commonly consumed vegetables is presented to address the problem of vitamin A deficiency. After a brief review of the prevalence of vitamin A deficiency and the efforts to reduce its incidence in Malawi, Moringa is suggested as a potential solution to the problem. A framework for designing nutrition intervention with Moringa is described for actual implementation. It is argued that attempts to identify, document, and encourage the utilization of nutrient-rich indigenous plants could be cost-effective, and a sustainable method of improving the nutritional status of local populations.